“They are English education graduates, but they teach science by using English”: A Mismatch between Policy and Practice? - Eddy Haryanto (Universitas Jambi, Indonesia, 2021)
In response to the issue of mismatched teachers teaching in international-based curriculum schools, this exploratory case study investigated the implementation of English teachers’ background teaching science by using English as a medium of instruction (EMI). Data were collected from six teachers who taught science through multiple interviews in one international-based curriculum school in Jambi city, Indonesia. The data presentations were done by making the data tabulation and grouping it into themes and sub-themes. The data tabulation is narrated in paragraph form to draw the content of the data tabulations. The findings revealed that mismatched teachers had problems to implement EMI in teaching science, such as lack of competencies in content knowledge, hard times to use English, and no training for curriculum changes. Despite the weakness, EMI creates international-minded and excels in English. Portraying these findings, recommendations are also discussed in this study.